Online counselling : a handbook for mental health professionals. - Kraus, Ron; Stricker, George; Speyer, Cedric (Practical resources for the mental health professional., 2010)
Providers and consumers of mental health services are increasingly making use of the internet to gather information, consult, and participate in psychotherapy. This Handbook gives practical insight into how professionals can translate their practice to an online medium. Divided into four sections, section one provides an overview of how the internet has become an integral part of people's lives, and the research to date on the use and effectiveness of counseling online, as well as idiosyncrasies of online behavior and communication. Section two discusses the "practical" aspects of counseling online, including technological issues, ethical and legal issues, and business issues. Section three focuses on performing psychotherapy online, including online treatment strategies and skills, working with online groups, online testing and assessment, and international and multicultural issues in online counseling. The last section discusses the future of online counseling. The Handbook is intended for those professionals interested in the burgeoning telehealth movement and to those practicing therapists looking for ways to expand their practices online and/or to help round out treatment to specific patients who might benefit from online therapy in addition to traditional delivery.